Nutritional behavior of cassava cultivars under influence of aluminum levels in nutrient solution - Oliveira, Luiz Edson Mota de; Rena, Alemar Braga (Pesquisa Agropecuaria Brasileira, 2014)
This study aimed to evaluate the nutritional behavior of three cassava cultivars (Manihot esculenta Crantz) (Branca de Santa Catarina, Vassourinha SEL-514 and Riqueza), under influence of 0,5 and 10 ppm of aluminum in nutrient solution. Differences in Al tolerance among the three cultivars, as well as file mechanism of toxic action of this cation were investigated. The amount of aluminum in the root system of the cultivars studied increased with the addition of this cation to the nutrient solution. However, in the leaf blade and petiole, only one cultivar showed increase in the content of aluminum whereas all other cultivars had not such alterations. The presence of aluminum, in the medium reduced P concentration in aerial parts, but increased this element in the root systems of all cultivars. Reductions in concentrations of potassium, calcium and Mg, duo to Al in the solution were on average, greater in the root systems than in aerial parts. In the roots, Al reduced mostly Mg, but in the aerial parts, Ca was more hardly reduced. Al also reduced both water absorption and water content of all three cultivars.